Computational Mechanistic Insights into Non-Cubane Iron-Sulfur Cluster-Dependent Enzymes with [2Fe–2S] and [4Fe–4S] Cores: A Review (Communications in Computational Chemistry, 2025)
Iron-sulfur ([FeS]) clusters are among the most ancient and functionallydiverse cofactors in biology, mediating processes ranging from electron transfer tosubstrate activation and catalysis. Within this broad class, non-cubane [FeS] clustersexhibit outstanding structural flexibility and chemical versatility. This review summarizesrecent computational advances in elucidating the mechanisms of non-cubane [FeS]cluster-dependent enzymes, focusing on systems containing [2Fe–2S] and distorted [4Fe–4S] clusters. Representative enzymes discussed include biotin synthase (BioB), Rieskedioxygenases (NDO, BphA, NBDO), heterodisulfide reductase (Hdr), and carbonmonoxide dehydrogenases (CODHs), that perform diverse chemical transformations suchas sulfur insertion, aromatic cis-dihydroxylation, S–S bond cleavage, and CO₂/CO interconversion. Special emphasis is placedon how quantum chemical cluster modelling and QM/MM simulations have provided insights into transient intermediates, rate-determining steps, and the roles of metal nuclearity and heterometal incorporation in tuning catalytic reactivity.